(untitled) (World Bulletin of Education and Learning, 2025)
This article examines the formative role of the Jadid movement in the emergence of modern Uzbek media at the beginning of the twentieth century. Drawing on historical and contemporary scholarly sources, it provides a narrative analysis of how Jadid intellectuals used newspapers, journals, and print culture to promote enlightenment, modern education, social reform, and national consciousness. The article highlights the ways in which Jadid publications introduced new journalistic genres, expanded public discourse, and helped standardize the emerging Uzbek literary language through innovative vocabulary and stylistic experimentation. Despite censorship, financial constraints, and limited literacy rates, the Jadid press succeeded in creating an early public sphere that encouraged debate, civic engagement, and cultural renewal. The study argues that the media practices shaped by the Jadids laid the foundation for the later development of Uzbek journalism and remain a significant part of the region’s intellectual and cultural heritage.